Interstitial Emphysema as a Rare Radiographic Presentation of Bronchial Dehiscence after Lung Transplant - Linda P. Vien; Robert M. Marron; Abbas Charlie; Maruti Kumaran; James C. Brown (Case Reports in Pulmonology)
Airway complications after lung transplantation are a major cause of morbidity and mortality. Bronchial dehiscence presents within a month of lung transplantation and is typically diagnosed radiographically as a sentinel gas pocket at the anastomotic site and confirmed with bronchoscopy. A 66-year-old man with idiopathic pulmonary fibrosis who underwent a right lung transplantation 4 weeks prior developed chest pain with palpable crepitus over his right chest wall. A chest X-ray revealed subcutaneous emphysema and a small right-sided pneumothorax. Computed tomography (CT) of the thorax without contrast revealed a gas pocket at the anastomotic site in the mediastinum as well as interstitial emphysema around the proximal bronchi of the right lung that had worsened when compared to CT from 11 days prior. A review of prior CT demonstrated interstitial emphysema without evidence of a sentinel gas pocket. These findings suggest that interstitial emphysema was the initial radiographic manifestation of the bronchial anastomotic site dehiscence. Interstitial emphysema is typically self-limiting, but severe cases can lead to major complications. Interstitial emphysema outside of the immediate postoperative period should be recognized as a possible early radiographic sign of bronchial dehiscence in lung transplant patients with vigilant monitoring of potential complications and strong consideration for early bronchoscopic investigation.